Nowe przestrzenie - komfortowe, funkcjonalne i bez barier = New Spaces - Comfortable, Functional, and Barrier-Free - Tarabuła, Joanna; Smycz, Katarzyna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Participation in the National Reading Development Program, Priority 2 "Library Infrastructure 2016-2020," and the implementation of the project "Renovation and Adaptation of the Municipal Public Library in Kostrzyn nad Odrą with Consideration of the Needs of Disabled Individuals" has enabled the creation of a welcoming cultural institution in Kostrzyn. It is an open space that fosters social interactions while also offering opportunities for relaxation and rest. The authors present the interesting spaces and the wide range of services that cater to users of all ages.
Keywords: przestrzeń biblioteczna; modernizacja; pracownie tematyczne; dostępność; książki; edukacja; współpraca; library space; modernization; thematic workshops; accessibility; books; collaboration